2006
DOI: 10.1007/s00428-006-0238-x
|View full text |Cite
|
Sign up to set email alerts
|

Oncofetal protein glypican-3 in testicular germ-cell tumor

Abstract: The expression of an oncofetal protein, the glypican-3 (GPC3), was immunohistochemically evaluated in a wide variety of primary testicular germ-cell tumors (GCTs) in comparison with other markers, alpha-fetoprotein (AFP), human chorionic gonadotropin (hCG)-beta, and OCT3/4. Eighty-nine cases of GCT including 22 cases of mixed GCT were evaluated with reference to each tumor component. GPC3 expression was observed in neoplastic cells of yolk-sac tumor (YST) (25/25), teratoma (2/10), components of syncytiotrophob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
54
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 21 publications
5
54
0
Order By: Relevance
“…The antibody to glypican-3 is known to be a specific marker for YSTs. Ota et al (15) reported that glypican-3 was positive in all cases of YST and in some cases of CC, teratoma and syncytiotrophoblastic giant cells, but in no case of EC. This may suggest that DNMT3L-and AFP-expressing seminoma cells have a YST-like phenotype or have already differentiated to YST cells Third, when examined in the present mixed GCTs, DNMT3L expression was observed in various subtypes other than EC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The antibody to glypican-3 is known to be a specific marker for YSTs. Ota et al (15) reported that glypican-3 was positive in all cases of YST and in some cases of CC, teratoma and syncytiotrophoblastic giant cells, but in no case of EC. This may suggest that DNMT3L-and AFP-expressing seminoma cells have a YST-like phenotype or have already differentiated to YST cells Third, when examined in the present mixed GCTs, DNMT3L expression was observed in various subtypes other than EC.…”
Section: Discussionmentioning
confidence: 99%
“…In an attempt to further clarify the phenotype of DNMT3L-positive seminoma cells, we conducted immunostaining with glypican-3, an oncofetal protein and a marker for extraembryonic differentiation, especially that of YSTs (15). In eight of the nine cases of DNMT3L-positive seminoma or seminoma elements examined, gypican-3 was negatively stained (Fig.…”
Section: Seminomasmentioning
confidence: 99%
“…32,[35][36][37] Recently, GPC3 has been reported to be overexpressed in testicular and ovarian yolk sac tumors. 25,26,32 Esheba et al reported that GPC3 immunohistochemistry is useful for distinguishing ovarian yolk sac tumors from clear cell adenocarcinomas because of the higher GPC3 expression in ovarian yolk sac tumors compared to clear cell adenocarcinomas. 32 Our results are similar to theirs in that most of yolk sac tumors showed diffuse GPC3 positivity, whereas only 10% of clear cell adenocarcinomas showed diffuse GPC3 positivity.…”
Section: 32mentioning
confidence: 99%
“…Its overexpression has been reported in certain types of tumors, such as hepatocellular carcinoma, 21,22 melanoma, 23 lung squamous cell carcinoma, 24 and testicular germ cell tumors. 25,26 GPC3 has also been reported to act as an immunohistochemical and serum marker for hepatocellular carcinoma and malignant melanoma. 21,23,27 In addition, it is now expected to be a potential target for immunotherapy against these neoplasms.…”
mentioning
confidence: 99%
“…In addition to the traditionally known fetoprotein and CD30 [11], 3 recently identified germ cell tumor-associated markers (SALL4, glypican 3, and CDX2) have been found to be useful [12,13]. Glypican 3 is an oncofetal antigen that is expressed in yolk sac tumors (100%) Fig.…”
Section: Discussionmentioning
confidence: 97%